2013
DOI: 10.1371/journal.pone.0053124
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Potential of Abandoned Military Areas Matches That of Established Reserves: Plants and Butterflies in the Czech Republic

Abstract: Military training generates frequent and irregular disturbance followed by succession, resulting in fine-scaled mosaics of ecological conditions in military training areas (MTAs). The awareness that MTAs may represent important biodiversity sanctuaries is increasing recently. Concurrently, changes in military doctrine are leading to abandonment of many MTAs, which are being brought under civilian administration and opened for development. We surveyed vascular plants in 43 and butterflies in 41 MTAs in the Czec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 34 publications
0
46
0
1
Order By: Relevance
“…In contrast to large disturbances which can completely destroy all communities (Cooke & Johnson, 2002;Dornelas, Soykan, & Ugland, 2010), small disturbances may enhance species richness by releasing resources and promoting the coexistence of species adapted to different conditions (Connell, 1978;Holt, 2008). Thus, disturbance -succession dynamics create highly heterogeneous, patchy conditions, which may generate resources for rich arrays of species (Cizek, Vrba, Benes, Hrazsky, & Koptik, 2013). Similar disturbance processes can be found also at other industrial sites, either terrestrial (Tropek et al, 2010 or even aquatic (Dolny & Harabis, 2012;Gray, Clarke, Warwick, & Hobbs, 1990;Ugland, Bjørgesaeter, Bakke, Fredheim, & Gray, 2008).…”
Section: Changes In Communities Over Time and Main Environmental Factorsmentioning
confidence: 93%
“…In contrast to large disturbances which can completely destroy all communities (Cooke & Johnson, 2002;Dornelas, Soykan, & Ugland, 2010), small disturbances may enhance species richness by releasing resources and promoting the coexistence of species adapted to different conditions (Connell, 1978;Holt, 2008). Thus, disturbance -succession dynamics create highly heterogeneous, patchy conditions, which may generate resources for rich arrays of species (Cizek, Vrba, Benes, Hrazsky, & Koptik, 2013). Similar disturbance processes can be found also at other industrial sites, either terrestrial (Tropek et al, 2010 or even aquatic (Dolny & Harabis, 2012;Gray, Clarke, Warwick, & Hobbs, 1990;Ugland, Bjørgesaeter, Bakke, Fredheim, & Gray, 2008).…”
Section: Changes In Communities Over Time and Main Environmental Factorsmentioning
confidence: 93%
“…The lower abundance and species richness of insects in anthropogenic habitats were reported repeatedly from many insect assemblages (Pereira et al ., ; Cardinale, ; Geslin et al ., ; Pereira‐Peixoto et al ., ), but the observations of reverse relationships are also known, particularly in a broad range of disturbance dependent species including, for example, various aculeate Hymenoptera (Cizek et al ., ; Tropek et al ., ; Heneberg et al ., ; Bogusch et al ., ). Here, we have shown that despite most of the dominant empty snail shell adopters among insects managed to colonise the anthropogenic habitats, they failed to establish there as large populations as in the natural habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Butterfly data for this study originated from a survey of 125 National Nature Reserves and National Natural Monuments, commissioned by the Nature Conservation Agency of the Czech Republic, and carried out in 2004–2006 (Benes and Konvicka , Cizek et al ). Czech National Nature Reserves/Monuments (NNR, herein ‘reserves’, total n = 221) are typically smaller localities, believed to cover most valuable nature sites in the country and administered by the central government; in addition to them, the Czech protected areas system includes four large‐sized National Parks, 25 large‐sized Protected Landscape Areas, and about 1800 small‐sized Regional Reserves.…”
Section: Methodsmentioning
confidence: 99%